Decline in Bone Mass With Tenofovir Disoproxil Fumarate/Emtricitabine Is Associated With Hormonal Changes in the Absence of Renal Impairment When Used by HIV-Uninfected Adolescent Boys and Young Men for HIV Preexposure Prophylaxis. (24th December 2016) - Havens, Peter L.; Stephensen, Charles B.; Van Loan, Marta D.; Schuster, Gertrud U.; Woodhouse, Leslie R.; Flynn, Patricia M.; Gordon, Catherine M.; Pan, Cynthia G.; Rutledge, Brandy; Liu, Nancy; Wilson, Craig M.; Hazra, Rohan; et al.
Summary: Tenofovir disoproxil fumarate (TDF)–based preexposure prophylaxis in human immunodeficiency virus–seronegative males, aged 15 to 22 years, is safe for kidneys. Disruption of parathyroid hormone–fibroblast growth factor 23–vitamin D control of calcium–phosphate balance is primarily linked with TDF-associated bone decline at this age. Abstract: Background: We aimed to define the relative importance of renal and endocrine changes in tenofovir disoproxil fumarate (TDF)–related bone toxicity. Methods: In a study of daily TDF/emtricitabine (FTC) preexposure prophylaxis (PrEP) in human immunodeficiency virus (HIV)–uninfected young men who have sex with men, we measured changes from baseline in blood and urine markers of the parathyroid hormone (PTH)–vitamin D–fibroblast growth factor 23 (FGF23) axis, creatinine, and renal tubular reabsorption of phosphate (TRP). We explored the relationship of those variables to changes in bone mineral density (BMD). Tenofovir-diphosphate (TFV-DP) in red blood cells was used to categorize participants into high and low drug exposure groups. Results: There were 101 participants, median age 20 years (range 15 to 22). Compared with low drug exposure, high-exposure participants showed increase from baseline in PTH and decline in FGF23 by study week 4, with no differences in creatinine, phosphate, or TRP. At 48 weeks, the median (interquartile range) percent decline in total hip BMD was greater in those with high- compared to low- exposure (−1.59 [2.77] vs +1.54 [3.34] %, respectively; P = .001); in high-exposure participants, this correlated with week 4 TFV-DP (inversely; r = −0.60, P = .002) and FGF23 (directly; r = 0.42; P = .039) but not other variables. Conclusions: These findings support the short-term renal safety of TDF/FTC PrEP in HIV-seronegative young men and suggest that endocrine disruption (PTH-FGF23) is a primary contributor to TDF-associated BMD decline in this age group. Clinical Trials Registration: NCT01769469.